2001
DOI: 10.1136/jech.55.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns among a national random sample of British adults

Abstract: Study objectives-To identify groups within the UK male and female population who report similar patterns of diet. Design-National representative dietary survey, using seven day weighed dietary records, of men and women aged 16-64 years living in private households in Great Britain in 1986-7. Cluster analysis was used to aggregate participants into diet groups. Setting-Great Britain. Participants-1087 men and 1110 women. Results-93% of men and 86% of women fell into one of four distinct diet groups. Among men t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
81
4
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 18 publications
20
81
4
2
Order By: Relevance
“…Based on the low energy intake, this group could also be called a low food energy group or low energy reporter (LER) group. Other studies have reported higher BMI in low energy groups (Pryer et al, 1997(Pryer et al, , 2001Fraser et al, 2000), but we did not find the same tendency in our LER group. However, we found a somewhat higher percentage of Bold numbers marks cluster with highest intake, underlined numbers marks clusters with lowest intake.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Based on the low energy intake, this group could also be called a low food energy group or low energy reporter (LER) group. Other studies have reported higher BMI in low energy groups (Pryer et al, 1997(Pryer et al, , 2001Fraser et al, 2000), but we did not find the same tendency in our LER group. However, we found a somewhat higher percentage of Bold numbers marks cluster with highest intake, underlined numbers marks clusters with lowest intake.…”
Section: Discussioncontrasting
confidence: 99%
“…The patterns we find in this study are similar to patterns found in several other studies. The Western pattern (Slattery et al, 1998;Fung et al, 2001;Terry et al, 2001) and the healthy pattern (or 'prudent pattern') are reported by many others (Slattery et al, 1998;Fung et al, 2001;Pryer et al, 2001;Terry et al, 2001;Chen et al, 2002;Newby et al, 2003), the same is the case for the alcohol pattern (Slattery et al, 1998;Terry et al, 2001;Newby et al, 2003) and the average pattern (or LER pattern) (Fraser et al, 2000;Greenwood et al, 2000;Millen et al, 2002). Several studies also report traditional diet patterns (Greenwood et al, 2000;Pryer et al, 2001;van Dam et al, 2003), but these are naturally different from the ones we find in our study since traditional patterns are specific to each country.…”
Section: Discussionsupporting
confidence: 51%
“…Consistent with other studies, we observed a relation between 'alcohol and meat products' pattern and smoking, low physical activity level and overweight, suggesting an aggregation of high-risk factors (Pryer et al, 2001;Tseng and DeVellis, 2001;Villegas et al, 2004;Engeset et al, 2005). In addition, we observed an association between the 'alcohol and meat products' pattern and the use of hypertensive and hyperlipidaemia medication among men in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Numerous studies have investigated relationships between sociodemographic characteristics, lifestyle and dietary patterns (Whichelow and Prevost, 1996;Greenwood et al, 2000;Pryer et al, 2001;Schulze et al, 2001;Tseng and DeVellis, 2001;Costacou et al, 2003;Sanchez-Villegas et al, 2003;Villegas et al, 2004;Bamia et al, 2005;Engeset et al, 2005;Park et al, 2005;Perrin et al, 2005;Yang et al, 2005;Pala et al, 2006). To our knowledge, only one study investigating the relationship between dietary patterns and their determinants was conducted in France, but among men only (Perrin et al, 2005), and there are no studies that have been carried out among French women and men.…”
Section: Introductionmentioning
confidence: 92%
“…This may reflect different reasons for the lower BMI, with the men with the lowest education having a lower BMI due to issues of inadequate access to food, while men with higher education have a lower BMI due to better food choices. While others have reported a similar independent association between education and diet quality and BMI and diet quality 22,25 , we are not aware of any analyses that have reported the variations in this association with stratification. However, these results must be viewed cautiously as the number of men in our lowest BMI category is small (n ¼ 59).…”
Section: Discussionmentioning
confidence: 48%